Contemporaneous east–west extension and north–south compression at 43 Ma in the Himalayan orogen - Zhou, Q.; Sun, H.; Evans, Noreen; Li, C.; Liu, Z.; Zhang, Q.; Yan, G.; Huang, J. (Pergamon-Elsevier Science Ltd., 2018)
It was previously proposed that the onset of east–west extension in the Himalayan orogen occurred after ca. 19 Ma. Here we present a Re–Os isochron age of ca. 43 Ma for sulfides from the Zhaxikang Zn–Pb–Sb–Ag polymetallic deposits, which occur within N–S–striking normal faults that reflect E–W extension in the Tethyan Himalayan orogen. This age is consistent with previously reported ages for regional metamorphism (ca. 48–42 Ma), granitoids (ca. 47–40 Ma) and gabbros (ca. 45 Ma) occurring along the Indus–Yarlung suture. In addition, this type of structure also broadly occurs in the Lhasa terrane, and plays a critical role in the Eocene porphyry–(skarn) copper polymetallic mineralization there. By ca. 45–43 Ma, the north–south–directed horizontal deviatoric stresses had peaked and subducted Neo–Tethyan slab breakoff had occurred at great depth, leading to abrupt slowdown of Indo–Asia convergence (ca. 45 Ma). E–W extension initially developed at shallow depths, resulting in formation of the north–south trending normal faults in the plateau. This type of extension would lead to collapse of the Tibetan plateau and decrease in altitude, subsequently resulted in Central Asian and the global climate changes. Our study places new constraints on the timing and nature of early Cenozoic tectonics and metallogenesis in the Himalayan orogen and climate changes in Central Asia.